Paradigms, Terminology, and Exegesis: Toward the Nonsupersessionist Reading of the New Testament - Henri Louis Goulet (Religions, 2025)
Interpretation of the New Testament (NT) in general and the Pauline corpus in particular still appears to be at a crossroads. Scholars continue to publish articles and monographs in binary opposition to one another. The terminology used to designate the overarching perspectives of these binary publications sharply contrasts a “traditional” perspective (Protestant in general, and Lutheran in particular) with a variously named “new” or “radical new” perspective. Most recently, beyond the imprecise “new” terminology, the non-traditional perspective is being referred to as the “post-supersessionist”, “nonsupersessionist”, or “within Judaism” perspective and is still strongly being contested. Historically speaking, these antithetical perspectives cannot both be completely correct. Arguably, then, the time has come to explore what the study of Kuhnian paradigms might reveal about this state of affairs in NT scholarship. Most important, in proffering a twofold hermeneutical way forward that is focused on better understanding the emic perspective of the texts that we interpret—to the extent humanly possible—it is hoped that we might become more keenly aware of the ethical implications of our paradigms, terminology, and exegesis for those who rely on our work for their understanding and appropriation of the Scriptures in their everyday living.